The Impact of group guidance in alleviating parental anxiety amidst the Menace of child abduction - Putra, Ahmad; Deliani, Nurfarida; Fitria, Anggi; Halim, Candra; Dzunuren, Arifal; Mulya, Sri (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2023)
Purpose - This research was conducted to see how the effectiveness of group guidance services in helping reduce the anxiety experienced by parents of SDN 41 Karang Tangah students regarding the issue of child kidnapping that is spread in the midst of society.Method - The type of research used is descriptive qualitative, the researchers involved 5 mothers of SDN 41 Karang Tangah students as group guidance participants with the aim of alleviating the anxiety experienced with the current issue of child abduction.Result - This topic at least generates several important points for parents, including: first, parents realize that advances in technology and social media make it easy for various issues to develop in the midst of society, second, parents find new knowledge and wise ways to deal with developing issues, third, parents understand that excessive anxiety will only lead to various forms of illness and weaken health conditions, fourth, parents understand how to properly supervise children, fifth, parents feel relieved and happy to be able to convey all aspirations and anxiety related to the growing issue of child abduction.Implication – Parents of students at SDN 41 Karang Tangah West Sumatra who were involved in group guidance activities discussed the topic of the task which was directly determined by the group leader with the topic